2020
DOI: 10.1002/rco2.28
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine pathway is associated with muscle anabolic effects by androgen receptor ligand

Abstract: Background Muscle wasting is a common condition concomitant with aging. Androgens significantly increase skeletal muscle mass, but the role of the androgen receptor (AR) in skeletal muscle is not well established. TEI‐SARM2, a novel selective androgen receptor modulator (SARM), was developed as a pharmaceutical candidate for the treatment of muscle wasting diseases. Methods The efficacy and specificity of TEI‐SARM2 were analysed in vitro assays, and efficacy was also evaluated in vivo using orchiectomized male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
3
1
Order By: Relevance
“…We found that AR was expressed in mesenchymal progenitors staining positive for PDGFRα (Fig. 1A), as well as in muscle fibers surrounded by laminin-expressing basal lamina, consistent with previous findings (17, 18).…”
Section: Resultssupporting
confidence: 92%
“…We found that AR was expressed in mesenchymal progenitors staining positive for PDGFRα (Fig. 1A), as well as in muscle fibers surrounded by laminin-expressing basal lamina, consistent with previous findings (17, 18).…”
Section: Resultssupporting
confidence: 92%
“…The ODC gene promotor contains an androgen response element [ 57 ], and when the androgen receptor is knocked out in mice, the ODC mRNA abundance is decreased [ 58 ]. Contrary to the present study, previous research in mouse skeletal muscle tissue shows that treatment with a selective androgen receptor modulator, a therapeutic compound that has anabolic effects similar to that of anabolic steroids without having the androgenic characteristics, results in an increased mRNA expression of ODC 14 d after treatment [ 51 ], which provides further evidence that an interaction between androgens and the polyamine biosynthetic pathway exists through ODC . However, the abundance of ODC in the proliferating cultures was unaffected by the treatment with polyamine precursors and was increased when cells were treated with Spe or Spd 0.5 and 12 h after treatment.…”
Section: Discussioncontrasting
confidence: 92%
“…Additionally, the effects of polyamines on proliferation rates of C2C12 cells from previous studies are inconsistent. Contrary to the observed results, a recent study found that the treatment of C2C12 cells with Put had no effect on proliferation rates 24, 48, 72, or 96 h post-treatment, but increased differentiation [ 50 ], while another study observed similar results to the present study and found that the treatment of C2C12 cells with concentrations of Spe that were less than those used in the present study (200, 600, or 2000 nM) increased proliferation rates 48 h post-treatment [ 51 ], indicating that Spe has a potent effect on proliferation. Additionally, the polyamine depletion of mouse fibroblasts cells results in an arrest of cell proliferation [ 52 ], demonstrating the importance of polyamines for proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, this could enhance the aging phenotype, such as decreased cell proliferation in primary myoblasts [60]. Other recent studies in mice and rats have shown the upregulation of spermidine/spermine N1-Acetyltransferase 1 when the AR is selectively modulated (by the agonist TEI-SARM2), hypothesizing that the hyperacetylation of polyamines could aid mitochondrial regulation for muscle function [98]. In blood samples from Japanese individuals, the spermine/spermidine ratio was shown to be inversely correlated with the progression of sarcopenia (Figure 2 and Table 1) [40].…”
Section: The Role Of Pas In Sarcopenia and Frailtymentioning
confidence: 99%